Vitis vinifera L. Pruning Waste for Bud-Preparations as Source of Phenolic Compounds–Traditional and Innovative Extraction Techniques to Produce New Natural Products - Dario Donno (MDPI AG, 2021)
Herbal products are now considered among the most important sources of phenolic compounds: the FINNOVER project aimed at the creation and development of sustainable supply chains to extract and use natural biologically active agents. Vitis vinifera is one of the most utilised herbal products derived from buds and sprouts as polyphenolic food supplements for its homeostatic and astringent properties. This research was aimed to describe the antioxidant capacity and the phytochemical composition of V. vinifera herbal products by the application of spectroscopic and chromatographic fingerprints considering phenolics as potential markers to significantly differentiate traditional preparations (macerates) from innovative extracts obtained by an ultrasound extraction from V. vinifera buds. Two different commercial products were also considered. Flavonols were the most abundant class in ultrasound extracts (45%), while phenolic acids were the most important class in traditional macerates (49%) and commercial bud-preparations (about 50%). This study may support the potential use of V. vinifera bud-products (starting from pruning byproducts) as food supplements to integrate human diet with good amounts of phenolics. Finally, the use of different extraction methods on the same plant material could be an important development to produce innovative herbal products with a phytochemical composition similar to traditional preparations.